Surfactant Catalyzed Oxidation of Ethanolamines by Cerium(IV) - Kumar Padhy, Ranjan; Das Bhattamisra, Sreelekha (Asian Journal of Chemistry, 2020)
Effect of surfactant medium on the kinetics of oxidation of amino alcohol by cerium(IV) has been reported. Two amino alcohols namely, monoethanolamine (MEA) and triethanolamine (TEA) are chosen for kinetic study. Sizeable changes in reaction rate are noted only in presence of sodium lauryl sulphate (NaLS) as surfactant. Both the amino alcohols exhibit rate maxima at around the cmc of NaLS, beyond which the kψ-[NaLS] profile shows slow increase in rate constant with increasing NaLS concentration. Suitable model has been used to explain the kinetic pattern post CMC and from this the micelle-reactant binding constant values have been evaluated. From the temperature dependence study, the activation parameters for the oxidation reactions have been computed and these are compared against those obtained for aqueous medium. Based on all information, plausible mechanism for micellar catalysis has been presented.